Juventude e política : conversas com o jovem eleitor de Jair Bolsonaro - Nascimento, Flávia dos Santos (2019)
In different countries of the world, the rise of right-wing policies has stood out through the strengthening of conservative organizations, evident in the United States with the election of Trump and, with the growth of conservative parties as in Spain and Argentina. Since May 2013, the streets have been once again spaces for political action and for the fight for rights. Throughout this period of demonstrations, while new conservative youth movements emerged, also new organizations with progressive agendas appeared. With this comes the desire to understand this social phenomenon that arises the idea of developing this research, and to conduct interviews with young voters in Bolsonaro, to hear what they have to say and try to understand how the young, ‘supposedly’ vehicle of change and progress, supposedly progressive almost by nature, can vote in Bolsonaro? What the hell happened?. This work was constructed from the method of research in psychoanalysis, the speeches of young people were analyzed through the psychoanalytic theoretical contribution. Through this study we perceive a prevalence of political use of affection, which marks the elections 2018, by an overflow of social tensions, a climate of politicization and discontent that has emerged in a polarized and radicalized campaign that remains dormant, as well as an affective mobilization of voters either by hate speech, fear, insecurity or hope.